2004
DOI: 10.1002/cne.11019
|View full text |Cite
|
Sign up to set email alerts
|

Inner retinal abnormalities in a mouse model of Leber's congenital amaurosis

Abstract: Leber's congenital amaurosis (LCA) is the earliest and most severe form in the world of genetic retinal dystrophy causing blindness. An animal model of LCA was recently created in which the cone-rod homeobox (crx) gene was disrupted using homologous recombination. Crx-/- mice display abnormal development of photoreceptors followed by their degeneration. We analyzed the morphology of inner retinal cells in crx-/- mice in order to evaluate the effects of abnormal photoreceptor development and death upon other re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 30 publications
7
47
1
2
Order By: Relevance
“…Retinal remodeling associated with photorececeptor degeneration as been reported by several groups in humans with RP (Fariss et al, 2000;Jones et al, 2003), as well as in animal models (Strettoi and Pignatelli, 2000;Fisher and Lewis, 2003;Marc et al, 2003;Pignatelli et al, 2004;Jones et al, 2005;Beltran et al, 2006). In this study, a striking finding was the prominent remodeling that occurred in the peripheral retina of XLPRA2 dogs following intravitreal injection of CNTF.…”
Section: Discussionsupporting
confidence: 70%
“…Retinal remodeling associated with photorececeptor degeneration as been reported by several groups in humans with RP (Fariss et al, 2000;Jones et al, 2003), as well as in animal models (Strettoi and Pignatelli, 2000;Fisher and Lewis, 2003;Marc et al, 2003;Pignatelli et al, 2004;Jones et al, 2005;Beltran et al, 2006). In this study, a striking finding was the prominent remodeling that occurred in the peripheral retina of XLPRA2 dogs following intravitreal injection of CNTF.…”
Section: Discussionsupporting
confidence: 70%
“…In addition to direct effects on photoreceptors, the rd͞rd mutation also results in alterations in inner retinal circuitry (32)(33)(34). Similar changes have also been reported in retinas of mice with mutations in the Leber's congenital amaurosis-causing gene Crx (35) and after simple visual deprivation (36,37). Recently, acute outer retinal degeneration has been reported to alter melanopsin expression levels in the inner retina of the rat (38,39).…”
Section: Pharmacologic Inhibition Of Visual Retinoid Cycle Causes Losmentioning
confidence: 59%
“…Previous work (Peng et al, 2003) has indicated that the rod bipolar cells might in fact receive ectopic input from remaining cone photoreceptors. While there is indication that with time there are substantial changes in inner retinal organization , Marc et al, 2003, Pignatelli et al, 2004, which may in part be the result of vascular pathology (Villegas-Pérez et al, 1998) but which has little to say for the early detailed circuit reorganization during the time course studied here.…”
Section: Discussionmentioning
confidence: 84%